Routing drone - Zheng, Min (2016)
In Drone routing, both the capability of the drone and the algorithm used for pathfinding are crucial in order to achieve a feasible and optimal complete tour. This project aims to build an approximation algorithm and a model, with the algorithm created as realistically as possible, being based on the state-of-the-art drone capability to suite the study on defining and controlling the flight path. The model provides the feasibility and optimization for drone routing, by modelling drone power recharging station as refueling depot nodes, delivery location as the target nodes and max flight time as the upper bound of the cost as a drone routing problem. The model is then solved using approximation algorithm.